Learning Quality Improvement through the Metacognitive Keywords Model (MKM) Teaching Model in Islamic Learning - Supa'at Supa'at; Khilman Rofi Azmi (Ijtimā`iyya: Journal of Muslim Society Research, 2019)
The dynamics of developmental technology and information in the Postglobalization era has a significant impact in building the scientific method of education, especially for Islamic Education. The teacher or Tutor as the main actor in delivering the learning material in the classroom is required to be able to map and guide students in understanding and implementing Islamic value. This article aims to developing PAI learning models through the Metacognitive Keyword Model (MKM). A teaching method intended for teachers / tutors so that they can guide their own thoughts in delivering the material appropriately, effectively and efficiently. The term "Keyword" refers to the â€œstressing pointâ€ of every material taught. MKM consists of several stages including (1) refresh; (2) re-arrange the keywords; (3) creating positive self talk or affirmation; (4) review and (5) Reflect. MKM can also be applied specifically to students through the keyword mapping process of each material. Through this model it is hoped that it will improve the quality of the learning process of Islamic Religion in educational settings.